Tsukushi is essential for the development of the inner ear - Toru Miwa; Kunimasa Ohta; Naofumi Ito; Satoko Hattori; Tsuyoshi Miyakawa; Toru Takeo; Naomi Nakagata; Wen-Jie Song; Ryosei Minoda (Molecular Brain, 2020)
Abstract Tsukushi (TSK)—a small, secreted, leucine-rich-repeat proteoglycan—interacts with and regulates essential cellular signaling cascades. However, its functions in the mouse inner ear are unknown. In this study, measurement of auditory brainstem responses, fluorescence microscopy, and scanning electron microscopy revealed that TSK deficiency in mice resulted in the formation of abnormal stereocilia in the inner hair cells and hearing loss but not in the loss of these cells. TSK accumulated in nonprosensory regions during early embryonic stages and in both nonprosensory and prosensory regions in late embryonic stages. In adult mice, TSK was localized in the organ of Corti, spiral ganglion cells, and the stria vascularis. Moreover, loss of TSK caused dynamic changes in the expression of key genes that drive the differentiation of the inner hair cells in prosensory regions. Finally, our results revealed that TSK interacted with Sox2 and BMP4 to control stereocilia formation in the inner hair cells. Hence, TSK appears to be an essential component of the molecular pathways that regulate inner ear development.